Bioprospecting for microorganisms of biotechnological importance in soils contaminated with agrochemicals - Costa, Celso Henrique Jorge; Ramos Filho, Antônio José; Sousa, Jennifer Slayder Santos; Castro, Érima Jôyssielly Mendonça; Pereira, Carlos Drielson da Silva; Miranda, Rita de Cassia Mendonça de (Ciência e Natura, 2018)
The aim of the present study was to isolate microorganisms from soils contaminated with agrochemicals and to evaluate their potential for biodegradation and production of bioactive metabolites. For this, microorganisms were isolated from a soil sample by the serial dilution technique using four different media: potato dextrose agar (PDA), Mueller Hinton agar (MH), malt extract agar (MEA), and Bushnell Haas agar (BH). The isolated microorganisms were identified by their macro and micromorphological characteristics and were tested for their ability to use the DMA 806 BR agrochemical, by the dichlorophenol indophenol (DCPIP) method. Biosurfactant production and antimicrobial activity were evaluated in the selected microorganisms. The emulsifying activity was evaluated by the emulsification index (IE24) technique, while the antimicrobial activity was evaluated through the solid medium assay against pathogens of clinical interest. Among the media tested, MEA yielded the highest number of isolates, as well as a greater diversity of microbial groups, with a predominance of bacteria. Of the selected microorganisms, ten had the ability to use the agrochemical. Of these ten microorganisms, five presented emulsifying activity and two presented the capacity to produce secondary metabolites. Among them, the J5 and B48 strains were distinguished by their emulsifying and antimicrobial activity.